2014
DOI: 10.1051/swsc/2014020
|View full text |Cite
|
Sign up to set email alerts
|

Scintillations of the GPS, GLONASS, and Galileo signals at equatorial latitude

Abstract: Small scale ionospheric disturbances can lead to fluctuations of the received satellite signal, so-called signal scintillations. For global navigation satellite systems (GNSS) this reduces the positioning accuracy. Particular strong events can even lead to a loss of lock between satellite and receiver. All GNSS signals are affected by this phenomenon. The influence of the short scale disturbances on the different GNSS signals is expected to be different for each signal, since the signals are transmitted by dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…As is well known (e.g. Basu and Basu, 1981;Aarons, 1982;Hlubek et al, 2014), signal scintillations could be observed in the evening hours after sunset.…”
Section: Monitoring Of Amplitude Scintillationsmentioning
confidence: 59%
See 1 more Smart Citation
“…As is well known (e.g. Basu and Basu, 1981;Aarons, 1982;Hlubek et al, 2014), signal scintillations could be observed in the evening hours after sunset.…”
Section: Monitoring Of Amplitude Scintillationsmentioning
confidence: 59%
“…Wiens et al, 2006). Using a single global navigation satellite system (GNSS) station, Hlubek et al (2014) have recently shown statistics of scintillation events occurring over the Bahir Dar region for GPS frequencies L1, L2C, and L5, GLONASS L1 and L2, and Galileo E1 and E5, covering the year 2013. These frequencies range between 1176.45 MHz (Galileo E5) and 1610.485 MHz (GLONASS L1).…”
Section: Introductionmentioning
confidence: 99%
“…The equatorial ionosphere with its complex dispersive features is of special interest in space weather research, which supports the operation of space‐based radio systems such as the Global Navigation Satellite System (GNSS) and remote sensing radars. The equatorial ionosphere is commonly characterized by the occurrence of enhanced GNSS signal scintillations in the evening hours (e.g., Hlubek et al, ; Kriegel et al, ). As has already been described many years ago, for example, by DasGupta et al (), the enhancement of amplitude scintillations is inherently associated with total electron content (TEC) depletions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Blanch et al () improved the characterization and modeling of plasma depletion by modifying a previously developed technique for detecting medium‐scale traveling ionospheric disturbances (Hernández‐Pajares et al, ). Based on former scintillation studies by Hlubek et al () and Kriegel et al () at Bahir Dar, we present a new method of describing plasma depletions, which are often associated with GNSS signal scintillations. Here, we focus on describing a new plasma bubble detection algorithm and demonstrating its practical value for automatized bubble detection (and the corresponding statistical analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the huge diversity of different structures within the ionosphere like plasma bubbles, patches, gradients Pradipta & Doherty (2016), traveling ionospheric disturbances (TIDs) (Borries et al, 2009) influence high frequency and trans-ionospheric radio wave propagation. So the associated impact causes amplitude and phase scintillation of GNSS signals Basu & Basu (1981), Béniguel et al (2009), Hlubek et al (2014), Kriegel et al (2017) and other ionospheric effects on space-based radar Xu et al (2004).…”
Section: Introductionmentioning
confidence: 99%